Aplikasi silika dan NAA terhadap pertumbuhan Anggrek Bulan (Phalaenopsis amabilis l.) pada tahap aklimatisasi - Ziadatul Choirum Nikmah; Widyati Slamet; Budi Adi Kristanto (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2017)
The purpose of the research was to study the influence silica and concentration of NAA for moon orchid (Phalaenopsis amabilis L.) growth in acclimatization. The experiment was assigned in completely randomized factorial design with the first factor was silica (non silika and with silica) and the second factor was NAA concentrations (0, 50, 100, and 150 ppm). Each treatments was repeated three times. Parameters measured were the percentage of plant life, number of leaves, length of leaf, width of leaf, number of roots, length of root and fresh weight of plants. Data were subjected to ANOVA and followed by Duncan Multiple Range Test. The result showed that aplication silica increased fresh weight of plants. Application of NAA concentrations (50, 100, and 150 ppm) decreased percentage of plant life, leaght of leaf, and fresh weight of plants. Interaction of silica and NAA concentrations showed did not significantly effect. Keyword : Moon orchid, silica, NAA, aclimatization